Acts & Resolves of Vermont, 25, no. 24, An Act to Prevent Traffic in Intoxicating Liquors for the Purpose of Drinking, §15 (1852). - (:unkn) unknown (General Publisher, 1852)
It shall be the duty of any sheriff, sheriff's deputy, constable, selectman, or grand juror, if he shall have information that any intoxicating liquor is kept or sold in any tent, shanty, hut or place of any kind for selling refreshments in any public place, except dwelling houses, on or near the ground of any cattle show, agricultural exhibition, military muster or public occasion of any kind, to search such suspected place without warrant, and if such officer shall find upon the premises any intoxicating liquor, he shall seize and apprehend the keeper or keepers of such place, and take them, with the liquor so found and seized, forthwith, or as soon as conveniently may be, before some justice of the peace of the town in which the same was found
--
Keywords: ARMED FORCES